QUALITY ASSESSMENT OF INSTRUCTION IN MATHEMATICS PROBLEM SOLVING CLASSES: AN EVALUATIVE INSTRUMENT (Revista Ifes Ciência, 2017)
This study aims at presenting our efforts to build a methodological tool to assess the quality of teaching in a math problem solving lesson based on Lesson Study method, and to contribute to practical orientation of the pre-service and in-service mathematics teachers. We rely on authors of mathematics education who studied problem solving, teaching practice and the performance of students. The instrument called “Quality Assessment of Instruction in Problem Solving” (QAIPS) was validated in the qualitative and interpretative ways. Some items that construct the instrument are here justified through empirical situations, which brought to the front discussions that expanded the analysis of the instrument. The QAIPS proved potential for the desired purposes.